Nutrition, lifestyle and colorectal cancer incidence: a prospective investigation of 10998 vegetarians and non-vegetarians in the United Kingdom. - Sanjoaquin, M; Appleby, P; Thorogood, M; Mann, J; Key, T (2004)
In a cohort of 10 998 men and women, 95 incident cases of colorectal cancer were recorded after 17 years. Risk increased in association with smoking, alcohol, and white bread consumption, and decreased with frequent consumption of fruit. The relative risk in vegetarians compared with nonvegetarians was 0.85 (95% CI: 0.55-1.32).